First observation of the decay B[bar]s0→D0K⁎0 and a measurement of the ratio of branching fractions B(B[bar]s0→D0K⁎0)/B(B[bar]0→D0ρ0) - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Holubyev, Kostya; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; et al. (Physics letters, 2011)
The first observation of the decay B¯s0→D0K⁎0 using pp data collected by the LHCb detector at a centre-of-mass energy of 7 TeV, corresponding to an integrated luminosity of 36 pb−1, is reported. A signal of 34.4±6.8 events is obtained and the absence of signal is rejected with a statistical significance of more than nine standard deviations. The B¯s0→D0K⁎0 branching fraction is measured relative to that of B¯0→D0ρ0: B(B¯s0→D0K⁎0)B(B¯0→D0ρ0)=1.48±0.34±0.15±0.12, where the first uncertainty is statistical, the second systematic and the third is due to the uncertainty on the ratio of the B0 and Bs0 hadronisation fractions.